EVALUASI AKUSTIK RUANG SALAT MASJID RAYA PINRANG - Saputra, Wahyu (JAMBURA Journal of Architecture, 2025)
Indonesia, as the country with the largest Muslim population globally, places a significant emphasis on the mosque as a central hub for religious, educational, and social activities. The acoustic performance of mosque interiors is a critical component of spatial quality, particularly to ensure speech intelligibility during sermons (khutbah), Qur’anic recitations, and other verbal religious practices. This study aims to evaluate the acoustic characteristics of Masjid Raya Pinrang’s main prayer hall by assessing three key parameters: sound pressure level (SPL), background noise level, and reverberation time (RT60). A descriptive quantitative approach was adopted. Field measurements were conducted using a Sound Level Meter 25TK (SLM25TK), connected to the Noise Logger Communication Tool (NLCT) for data recording and analysis. SPL measurements were taken during Friday sermons, while noise levels were recorded over three days (Monday, Friday, Sunday) at five different time intervals to capture varying environmental conditions. Reverberation time was calculated using the Sabine equation, based on the room’s volume and surface absorption values. The results indicate that the average SPL ranged between 98.98 and 100.48 dB, exceeding the acoustic comfort range for worship spaces. Ambient noise levels also surpassed the permissible thresholds outlined in the Indonesian Ministry of Environment Decree No. 48/1996. Furthermore, RT60 values at 500 Hz and 1000 Hz were recorded at 4.71 and 4.67 seconds, respectively, significantly exceeding the ideal range for speech-dominant functions. These findings suggest a need for targeted acoustic interventions to enhance speech clarity and overall auditory comfort within the prayer space.